2012
DOI: 10.3171/2012.8.jns122
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of vagus nerve stimulation in posttraumatic versus nontraumatic epilepsy

Abstract: Object In the US, approximately 500,000 individuals are hospitalized yearly for traumatic brain injury (TBI), and posttraumatic epilepsy (PTE) is a common sequela of TBI. Improved treatment strategies for PTE are critically needed, as patients with the disorder are often resistant to antiepileptic medications and are poor candidates for definitive resection. Vagus nerve stimulation (VNS) is an adjunctive treatment for medically refractory epilepsy that results in a ≥ 50% reduction in seizure frequency in appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 32 publications
2
30
0
Order By: Relevance
“…Favorable response to therapy, with ≥50% reduction in seizure frequency, was reached by 1972 of 4483 (44%) patients after three months of therapy, and by 618 of 1104 (56%) patients after 24 months. Patients with a history of Lennox-Gastaut syndrome or epilepsy stemming from a traumatic source may benefit from an improved treatment response [50]. Adverse events associated with VNS include hoarseness (37–62%), cough (7–21%), pain (6–17%), and infection (4–6%) [67,29,10,42].…”
Section: Neurostimulation Proceduresmentioning
confidence: 99%
“…Favorable response to therapy, with ≥50% reduction in seizure frequency, was reached by 1972 of 4483 (44%) patients after three months of therapy, and by 618 of 1104 (56%) patients after 24 months. Patients with a history of Lennox-Gastaut syndrome or epilepsy stemming from a traumatic source may benefit from an improved treatment response [50]. Adverse events associated with VNS include hoarseness (37–62%), cough (7–21%), pain (6–17%), and infection (4–6%) [67,29,10,42].…”
Section: Neurostimulation Proceduresmentioning
confidence: 99%
“…(2012) retrospectively compared outcomes of VNS in patients with post-traumatic epilepsy (PTE) and those with non-traumatic epilepsy. The group found PTE patients to have larger reductions in seizure frequency and a greater clinical response compared to non-traumatic epileptics [181]. Current pilot studies by Dr. Samadani and colleagues to understand prospective clinical outcomes in patients who receive a VNS after TBI are underway and successful work would pave the way for larger trials [182].…”
Section: Seizure Treatmentsmentioning
confidence: 99%
“…Two surgical intervention studies were identified for the treatment of adults with PTE . One study was a retrospective case‐control study of 317 adults with drug‐resistant PTE compared with 1,763 patients with drug‐resistant non‐PTE who were treated with a vagal nerve stimulator (VNS) (Table ) .…”
Section: Resultsmentioning
confidence: 99%
“…Two surgical intervention studies were identified for the treatment of adults with PTE . One study was a retrospective case‐control study of 317 adults with drug‐resistant PTE compared with 1,763 patients with drug‐resistant non‐PTE who were treated with a vagal nerve stimulator (VNS) (Table ) . Englot et al reported a significant reduction in seizures (of 73% at 2 years follow‐up) following VNS therapy in people with PTE, which was higher than that in patients treated for non‐PTE (61%).…”
Section: Resultsmentioning
confidence: 99%